Determination of Dissociation Constants for the Interaction of Myosin-5a with its Cargo Protein Using Microscale Thermophoresis (MST) - Rui Zhou; Jiabin Pan; Xiang-Dong Li (Bio-Protocol)
Myosin-5a (Myo5a) is an actin-dependent molecular motor that recognizes a diverse range of cargo proteins through its tail domain, playing a crucial role in the transport and localization of various organelles within the cell. We have identified a new interaction between Myo5a and its cargo protein melanophilin (Mlph), i.e., the interaction between the middle tail domain of Myo5a (Myo5a-MTD) and the actin-binding domain of Mlph (Mlph-ABD), by GST pulldown assay. We then intend to obtain the dissociation constant between Myo5a-MTD and Mlph-ABD using isothermal titration calorimetry (ITC) or microscale thermophoresis (MST), both of which are two commonly used methods for determining quantitative data on protein interactions. The advantages of MST over ITC include less protein usage, shorter operation time, and higher sensitivity. In this protocol, we present a method for using MST to determine the dissociation constants of Myo5a-MTD and Mlph-ABD, which were purified through overexpression in bacteria using affinity chromatography. The dissociation constant values obtained directly reflect the binding strength between these two proteins and provide a foundation for the isolation and purification of the complex in the future.